Compatibility of inseticides with the entomopathogenic fungus Metarhizium rileyi (Ascomycota) (Research, Society and Development, 2022)
Currently, there are numerous chemical substances on the market used to control insect pests. Among them, insecticides are a numerous and prominent group. The objective of this work was to evaluate "in vitro" compatibility between insecticides Permethrin (Pounce®) and Acephate (Orthene®) and strains UFMS 06 and UFMS 07 of the fungus Metarhizium rileyi. Mycelial growth, spore production, and spore germination were evaluated. After solidifying the culture medium containing the insecticides, the fungus M. rileyi was inoculated and incubated for 7 days in an acclimatized chamber at 25±1 ºC, 70±10% relative humidity, and 12-hour photoperiod. For spores’ germination, the incubation period was 20 hours, under the same conditions mentioned above. Biological index was used to establish the toxicological classification of insecticides on the fungus. The results showed that the products tested were classified as compatible, being compatible with the entomopathogenic fungus. Therefore, the products tested are recommended for use in the integrated management of agricultural pests as they do not affect the development of the biological control agent M. rileyi.